Genetic diversity of strawberry germplasm using metabolomic biomarkers. - Vallarino, José G.; De Abreu e Lima, Francisco; Soria, Carmen; Tong, Hao; Pott, Delphine M.; Willmitzer, Lothar; Fernie, Alisdair R.; Nikoloski, Zoran; Osorio-Algar, Sonia (Springer Nature, 2018)
High-throughput metabolomics technologies can provide the quantification of metabolites levels across various biological processes in different tissues, organs and species, allowing the identification of genes underpinning these complex traits. Information about changes of metabolites during strawberry development and ripening processes is key to aiding the development of new approaches to improve fruit attributes. We used network-based methods and multivariate statistical approaches to characterize and investigate variation in the primary and secondary metabolism of seven domesticated and seven wild strawberry fruit accessions at three different fruit development and ripening stages. Our results demonstrated that Fragaria sub-species can be identified solely based on the gathered metabolic profiles. We also showed that domesticated accessions displayed highly similar metabolic changes due to shared domestication history. Differences between domesticated and wild accessions were detected at the level of metabolite associations which served to rank metabolites whose regulation was mostly altered in the process of domestication. The discovery of comprehensive metabolic variation among strawberry accessions offers opportunities to probe into the genetic basis of variation, providing insights into the pathways to relate metabolic variation with important traits.
Keywords: Fresas - Germoplasma; Metabolitos vegetales; Strawberry; Germplasm; Fruit; Metabolomics